Relationship between Predisposing Factors and Compliance with the Use of PPE (Personal Protective Equipment) among Workers at Steel Industry of PT X - Aji Saputra; Evi Widowati (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Predisposing factors in this paper refer to factors that facilitate compliance behavior in the use of PPE in the workplace. This study aims to determine the relationship between predisposing factors of age, years of service, attitudes and knowledge with the compliance with the use of PPE at PT X. This study applied a cross-sectional approach. The sample size was 60 workshop workers. This study was conducted from November 2022 to February 2023. The instruments were questionnaire and observation sheet. The chi-square test results showed that age (p=0.517) and years of service (p=0.530) showed no relationship with the use of PPE. Furthermore, there was a relationship between compliance with the use of PPE among workers with knowledge (p=0.016) and attitude (p=0.006). The result of multivariate analysis test showed that knowledge (p=0.035) and attitude (p=0.013) significantly affected compliance with the use of PPE. In addition, it was found that there was a relationship between knowledge and attitudes with compliance with the use of PPE. Companies need to improve the leadership style of supervisors through influencing and motivating workers. Several practices involve providing a sense of comfort, supporting workers while working or using PPE, so that workers can positively influence other workers in carrying out the company's vision and mission and using PPE to reduce accident rates.